Courts and Business Registration : Evidence from Serbia - Bruhn, Miriam; Cho, Caleb; Marusic, Andreja; Nguyen, Ha; Reyes, Jose-Daniel; Tran, Trang (World Bank, Washington, DC, 2018)
This paper studies the effects of a reform in Serbia that transferred business registration from regional courts to a centralized agency. Using administrative data, the analysis employs a difference-in-difference strategy that compares new firms before and after the reform across districts based on the level of distrust in regional courts. The results suggest that the reform increased the number of new firms more in regions with higher initial levels of distrust, by up to 34 percent. The reform also increased the survival rates of new firms. These effects are large compared to those of other types of registration reforms, suggesting that courts can pose significant barriers to new firm creation.